IMPROVING EARLY CHILDHOOD MOTOR SKILLS THROUGH THE PLAYING ARTS AND CRAFTS METHOD AT RA NUR RAHMA CILEUNYI - Herlina; Hasyim, Ibnu (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Early childhood is a golden age, where the first year of growth and development begins and is ongoing, including physical and physiological development. One of the achievements of rapid growth and development in early childhood is their physical motor skills, so this plays a very important role for parents and educators to facilitate various activities. Early Childhood Education Institutions (PAUD) are a place to develop children's creativity and skills with a competency-based curriculum that includes aspects of development including the development of abilities, behavior and independence. However, there are several children who are seen at RA Nur Rahma who have difficulties when doing their motor activities, so further research is needed, this research was carried out in two cycles and two meetings in class. The game is carried out in 2 stages, namely pre-game and core game, based on the results obtained in cycle II, the second meeting, children's fine motor skills have increased with a percentage score of 100%.